Biofilm dispersal patterns revealed using far-red fluorogenic probes. - Jojo A Prentice; Sandhya Kasivisweswaran; Robert van de Weerd; Andrew A Bridges (PLoS Biology)
Bacteria frequently colonize niches by forming multicellular communities called biofilms. To explore new territories, cells exit biofilms through an active process called dispersal. Biofilm dispersal is essential for bacteria to spread between infection sites, yet how the process is executed at the single-cell level remains mysterious due to the limitations of traditional fluorescent proteins, which lose functionality in large, oxygen-deprived biofilms. To overcome this challenge, we developed a cell-labeling strategy utilizing fluorogen-activating proteins (FAPs) and cognate far-red dyes, which remain functional throughout biofilm development, enabling long-term imaging. Using this approach, we characterize dispersal at unprecedented resolution for the global pathogen Vibrio cholerae. We reveal that dispersal initiates at the biofilm periphery and approximately 25% of cells never disperse. We define novel micro-scale patterns that occur during dispersal, including biofilm compression during cell departure and regional heterogeneity in cell motions. These patterns are attenuated in mutants that reduce overall dispersal or that increase dispersal at the cost of homogenizing local mechanical properties. Collectively, our findings provide fundamental insights into the mechanisms of biofilm dispersal, advancing our understanding of how pathogens disseminate. Moreover, we demonstrate the broad applicability of FAPs as a powerful tool for high-resolution studies of microbial dynamics in complex environments.